Diseño estructural de un puente sobre la quebrada de Shatoja - Águila Panduro, Artemio Del (2001)
There are many destructive history of the Sisa River, which makes villagers to fear a further disaster in the presence of large avenues. For this is necessary that them way of access to the District of Shatoja and San Martin is are operating, being an obstaeulo main it broken Shatoja, that is located in the District of the same name and that gives access to them two districts mentioned, since before a great Avenue leaves isolated to the District of San Martin and part of the District of Shatoja of the rest of the province This being the only land access route, for this reason is chose the design of a bridge under the described features later after be compared cQn_diferentes types of bridges. The project consists of designing the superstructure and substructure of a bridge section made of steel and concrete. In the development of the project methodology design and the solutions adopted for the different cases, previously held the di...